2016
DOI: 10.3390/ijms17020260
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone-Induced Apoptosis through Caspase-Dependent Intrinsic Pathways in Human Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most commonly diagnosed cancers worldwide. Chemoprevention of HCC can be achieved through the use of natural or synthetic compounds that reverse, suppress or prevent the development of cancer progression. In this study, we investigated the antiproliferative effects and the mechanism of action of two compounds, 2,3,4′-trimethoxy-2′-hydroxy-chalcone (CH1) and 3′-bromo-3,4-dimethoxy-chalcone (CH2), over human hepatoma cells (HepG2 and Huh-7) and cultured mouse hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 64 publications
0
23
0
1
Order By: Relevance
“…Among the caspases that function as important regulators of apoptosis, caspase-3, a major effector in apoptosis progression, interacts with caspase-9 and caspase-8. In previous studies using HCC cells, the activation of caspase-9, caspase-8 and caspase-3 was investigated to evalutate caspase-dependent apoptosis 16,17. We found that imatinib and GNF5 induced caspase-mediated apoptosis, and slightly increased p27 and p21 protein level in SK-HEP1 cells.…”
Section: Discussionmentioning
confidence: 88%
“…Among the caspases that function as important regulators of apoptosis, caspase-3, a major effector in apoptosis progression, interacts with caspase-9 and caspase-8. In previous studies using HCC cells, the activation of caspase-9, caspase-8 and caspase-3 was investigated to evalutate caspase-dependent apoptosis 16,17. We found that imatinib and GNF5 induced caspase-mediated apoptosis, and slightly increased p27 and p21 protein level in SK-HEP1 cells.…”
Section: Discussionmentioning
confidence: 88%
“…Among these, apoptosis and necrosis are the most common and studied ones. Apoptosis events have been induced by chalcones towards different cancer cell lines 36,37 . In order to investigate antiproliferative effect mechanism of selected chalcones 11 and 17 towards MCF-7 and MDA-MB-231 lines, Annexin V/PI staining and flow cytometry were used to detect whether cells were dying due to apoptosis or necrosis events (Figure 2).…”
Section: Pro-apoptotic Activity Of Selected Chalcones 11 and 17mentioning
confidence: 99%
“…The vital roles of chalcones include anticancer activity, anti‐inflammatory activity, antibacterial activity, antituberculosis activity, antidiabetic activity, antioxidant activity, antimicrobial activity, antiviral activity, antimalarial activity, neuroprotective effects, and others . Although, chalcones show antiproliferative activity through up regulation of caspase signaling cascade that will activate the mitochondrial intrinsic pathways and promotes apoptotic cell death, recent investigation suggest that chalcones enhance the cancer cell death though the G0/G1 and S phase arrest . In continuation of our work, we reported novel thiophene based chalcone scaffolds as apoptosis‐inducing anticancer agents in cancer therapy (Figure ).…”
Section: Introductionmentioning
confidence: 99%